Analisis Kemampuan Komunikasi Matematis Siswa Kelas VIII-9 MTsN 1 Bukittinggi - Putra, Ilham Yani; Medika, Gema Hista; Isnaniah; Rahmat, Tasnim (Papanda, 2025)
The purpose of this study was to evaluate students' mathematical communication skills in grades VIII-9 at MTsN 1 Bukittinggi. The approach used was descriptive quantitative, with implementation on May 6, 2024, and involving 32 students through purposive sampling techniques based on information from teachers regarding their low abilities. The data collection instrument was a descriptive test with 4 questions that reflected three indicators: connecting objects with mathematical concepts; expressing mathematical ideas, situations, and relationships; and expressing events or ideas in mathematical symbols. The results of the analysis showed that in general, students' mathematical communication skills were in the